2001
DOI: 10.1002/hbm.10006
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis for sentence comprehension: Grammatical and short‐term memory components

Abstract: We monitored regional cerebral activity with BOLD fMRI while subjects were presented written sentences differing in their grammatical structure (subject-relative or object-relative center-embedded clauses) and their short-term memory demands (short or long antecedent-gap linkages). A core region of left posterior superior temporal cortex was recruited during all sentence conditions in comparison to a pseudofont baseline, suggesting that this area plays a central role in sustaining comprehension that is common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
196
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(218 citation statements)
references
References 63 publications
21
196
1
Order By: Relevance
“…. Other studies have also suggested that the left IFG activation reflects short-term memory demands [Cooke et al, 2002;Fiebach et al, 2005]. In our previous study, however, we directly compared the cortical activations in syntactic decision tasks with those in verbal short-term memory tasks and observed that the left dF3t showed selective activation for syntactic decisions in sentences, and that this activation was much greater than would be expected merely due to task difficulty and verbal shortterm memory demands [Hashimoto and Sakai, 2002].…”
Section: Discussionmentioning
confidence: 62%
“…. Other studies have also suggested that the left IFG activation reflects short-term memory demands [Cooke et al, 2002;Fiebach et al, 2005]. In our previous study, however, we directly compared the cortical activations in syntactic decision tasks with those in verbal short-term memory tasks and observed that the left dF3t showed selective activation for syntactic decisions in sentences, and that this activation was much greater than would be expected merely due to task difficulty and verbal shortterm memory demands [Hashimoto and Sakai, 2002].…”
Section: Discussionmentioning
confidence: 62%
“…In comparison to the anterior regions, we did not observe any activation related to syntactic surprisal in the left posterior STS/STG. This region has historically been less associated with syntactic processing compared to anterior regions, though fMRI activation related to syntax is sometimes observed (Constable et al, 2004;Cooke et al, 2002;Hasson et al, 2006;Tyler et al, 2011). Constable et al (2004) and Cooke et al (2002) both used an object-versus subject-relative clause comparison in their studies, and Hasson et al (2006) compared subordinate-clause sentences (many of which included relative clauses) to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the left anterior temporal lobe (ATL) has often been linked to computations related to the manipulation of syntactic structure (Brennan et al, 2010;Dronkers et al, 2004;Friederici et al, 2000a;Friederici et al, 2000b;Humphries et al, 2005;Humphries et al, 2006;Mazoyer et al, 1993;Noppeney and Price, 2004;Rogalsky and Hickok, 2009;Tyler et al, 2011;Vandenberghe et al, 2002). Finally, several studies suggest a potential role for left posterior superior temporal sulcus and gyrus (STS/STG) in syntactic processing (Constable et al, 2004;Cooke et al, 2002;Hasson et al, 2006;Tyler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(Caplan et al, 2000;Inui et al, 1998;Just et al, 1996;Stromswold et al, 1996)), more recent studies have postulated that this area may be related more to syntactic working memory rather than syntactic complexity (Fiebach et al, 2001;Fiebach et al, 2005); during the processing of a syntactically complex sentence the displaced element must be maintained in working memory over a prolonged distance (Friederici et al, 2003). While it has previously been proposed that dislocated elements in sentence processing are maintained as semantic representations (Cooke et al, 2002) without a phonologic element, that study displayed activation in BA 47, associated with semantic processing (Bookheimer, 2002), as opposed to the BA 44/45 seen in the current study. The region of Broca's area (Figure 1c) recruited in the current study is the more posterior aspect, thought to be involved with phonological/syntactic, rather than semantic, processing (Cannestra et al, 2000).…”
Section: Discussionmentioning
confidence: 99%